DAMPAK ACFTA (ASEAN-CHINA FREE TRADE AREA) TERHADAP PERDAGANGAN BUAH JERUK LOKAL DI INDONESIA (Impact of ACFTA (Asean-China Free Trade Area) On Trade Local Citrus Indonesia) - Rizki Gemala Busyra (Universitas Batanghari Jambi, 2015)
Indonesia is one of the central of oranges in the world. In 2010 the government issued the reduction in import tariffs on oranges fruits in Indonesia. This reduction will affect the sales of the local oranges fruit Indonesia. The purpose of this study is to identify the factors that affect the import, productivity, consumtion, area and the price of orange in Indonesia, and to analyze the impact of ACFTA on oranges fruit sales in Indonesia. This study employs an econometric model consisting of 5 structural equations and 2 identity equations. This study uses secondary data is structured as time series data, starting 1986 until 2010. The result of this study shows the reduction of import tarrif will increase import oranges in Indonesia, and the consumption the local oranges will be decrease.Keywords: Econometric Model, Citrus, Indonesia